Manajemen Event Talk Show Virtual Oleh Pt Pilihanmu Indonesia Jaya - Riqqah, Aisyah Zahra; Akbar, Djuni; Rudatin, Christina L. (Bisnis Event, 2024)
The process of choosing a major plays a very important role in shaping the career and academic development of prospective students. Geographical factors and limited physical access can be an obstacle for prospective students outside the region to attend events held in person. In the digital era, technology and education have become a major unity as a tool of the present through the use of digital platforms. The talk show titled "Piljurian Talk #2" by Student Ambassadors of Select Majors aims to provide information about lectures in general, provide opportunities for prospective students to interact directly with speakers and experienced students, and create a more personal and in-depth experience. During the session, analysis and observation from the preparation stage to the evaluation stage showed an understanding of the production and logistics functions in the Piljurian Talk #2 virtual event management process. In the preparation, organizing, implementing, and controlling stages, the production and logistics of Piljurian Talk #2 were carried out in accordance with the plan that had been prepared.